2013
DOI: 10.1371/journal.pgen.1003213
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Degradation of Replisome Components Ensures Genome Stability upon Replication Stress in the Absence of the Replication Fork Protection Complex

Abstract: The stabilization of the replisome complex is essential in order to achieve highly processive DNA replication and preserve genomic integrity. Conversely, it would also be advantageous for the cell to abrogate replisome functions to prevent inappropriate replication when fork progression is adversely perturbed. However, such mechanisms remain elusive. Here we report that replicative DNA polymerases and helicases, the major components of the replisome, are degraded in concert in the absence of Swi1, a subunit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 98 publications
(142 reference statements)
5
46
0
Order By: Relevance
“…Mrc1 also functions in coordination of polymerase and helicase functions at the fork 51 . As in the case of Dia2, we found that Pof3 is involved in Mrc1 degradation 26 . It is widely known that SCF-type ubiquitin ligases recognize phosphodegrons 39 .…”
Section: Regulation Of Mrc1 Degradation By Scfpof3 and Phosphorylationsupporting
confidence: 61%
See 2 more Smart Citations
“…Mrc1 also functions in coordination of polymerase and helicase functions at the fork 51 . As in the case of Dia2, we found that Pof3 is involved in Mrc1 degradation 26 . It is widely known that SCF-type ubiquitin ligases recognize phosphodegrons 39 .…”
Section: Regulation Of Mrc1 Degradation By Scfpof3 and Phosphorylationsupporting
confidence: 61%
“…pof3 ∆ cells also displayed a cell elongation phenotype, which is normally caused by accumulation of DNA damage or replication failure. Consistently, pof3 ∆ cells showed a delay in replication recovery after a low-dose CPT treatment, which did not affect replication recovery in wild-type cells 26 . Interestingly, Pol2 overexpression is deleterious to the cells (data not shown).…”
Section: Role Of Scfpof3-dependent Pol2 Degradation In Faithful Dna Rmentioning
confidence: 60%
See 1 more Smart Citation
“…Indeed, a more recent study has identified additional novel pathways that lead to replication factor degradation in response to replisome instability (Roseaulin et al 2013). These effects on replisome integrity suggest that replication fork collapse in cells deficient in the Mec1-Rad53 (S. cerevisiae), Rad3-Cds1 (S. pombe), or ATR-CHK1 (metazoans) pathways may be caused initially by the targeted disengagement of replisome components.…”
Section: Failure To Restart Replication In Atr-deficient Cells Coincimentioning
confidence: 99%
“…This method can be used to amplify specific chromosomal loci, in order to measure the quantity of DNA precipitated with the antibodies. Examples of this analysis are shown in our previous studies [3739].

Mix the following (for 1 sample):

2 μL of template DNA (input or ChIP DNA) ( see Note 23 ).

5 μL of iQ SYBR Green Supermix.

0.3 μL of forward primer (10 μM) ( see Note 7 ).

0.3 μL of reverse primer (10 μM) ( see Note 7 ).

2.4 μL of H 2 O.

Perform PCR using the following program.

95 °C for 2 min.

95 °C for 10 s.

55–60 °C for 30 s.

72 °C for 30 s (perform SYBR Green detection).

Repeat above steps ( b )–( d ) for 39 cycles.

72 °C for 7 min.

(Optional) Melting curve analysis: 55–95 °C.

Obtain cycle threshold (Ct) values for each sample.

Calculate % precipitated DNA using ∆Ct values between WCE and ChIP samples using the following equations:

Calculate dilution factor.

…”
Section: Methodsmentioning
confidence: 99%